Development of the Ruangverse Interactive Website Based on Project-Based Learning and Deep Learning to Enhance Students’ Understanding of Solid Geometry Concepts - Aulyanissa Tsaqifa Maharshall; Heni Pujiastuti (Universitas Muhammadiyah Surabaya, 2026)
This study aimed to develop and evaluate the feasibility of the RuangVerse interactive website, which integrates Project-Based Learning (PjBL) and Deep Learning principles for learning solid geometry to support students’ conceptual understanding. This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of the analysis, design, development, implementation, and evaluation stages. The research participants included three expert validators (content, media, and language experts) and 33 seventh-grade students at SMPN 1 Bayah. Data were collected using validation sheets, teacher and student response questionnaires, and a conceptual understanding test. The results showed that the RuangVerse website achieved a validity score of 91%, indicating that it was highly valid for learning use. The practicality assessment yielded scores of 99% from teachers and 90% from students, both categorized as very practical. Furthermore, students’ conceptual understanding improved after using RuangVerse, as reflected by an average N-Gain score of 0.89, which falls into the high category. These findings indicate that RuangVerse has the potential to support the improvement of students’ conceptual understanding of solid geometry through interactive, project-based, and meaningful learning experiences. Therefore, RuangVerse can serve as an innovative mathematics learning medium that supports active and contextual learning in the digital era.